2003
DOI: 10.1128/jb.185.8.2611-2617.2003
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of the Neisseria meningitidis Secretin PilQ Determined from Negative-Stain Transmission Electron Microscopy

Abstract: The PilQ secretin from the pathogenic bacterium Neisseria meningitidis is an integral outer membrane protein complex which plays a crucial role in the biogenesis of type IV pili. We present here the first three-dimensional structure of this type of secretin at 2.5-nm resolution, obtained by single-particle averaging methods applied to the purified protein complex visualized in a negative stain. In projection, the PilQ complex is circular, with a donut-like appearance. When viewed from the side it has a rounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 55 publications
6
73
0
1
Order By: Relevance
“…Secretins are multimeric OM proteins in which a conserved C-terminal ␤-barrel rich domain is implicated in forming the multimeric OM channel (39 -42). Typically, 6 -14 identical subunits form the ringlike structure of the secretin (39,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Despite similarities in overall architecture of the secretin and Wza multimers, the respective monomers share no primary sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretins are multimeric OM proteins in which a conserved C-terminal ␤-barrel rich domain is implicated in forming the multimeric OM channel (39 -42). Typically, 6 -14 identical subunits form the ringlike structure of the secretin (39,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Despite similarities in overall architecture of the secretin and Wza multimers, the respective monomers share no primary sequence similarity.…”
Section: Discussionmentioning
confidence: 99%
“…The channels formed by protein export secretins are gated (48,55), and low resolution three-dimensional structures of three secretins suggest an open state for these channel proteins in the OM and a closed state in the periplasm entrance (42,44,49). Gated channels are also formed by TolC, an outer membrane protein involved in type I protein secretion and multidrug efflux (56).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of the PilQ complex from meningococcal outer membranes was performed as previously described (Collins et al, 2001(Collins et al, , 2003(Collins et al, , 2004.…”
Section: Construction Of Meningococcal In-frame Pilq-his Fusionsmentioning
confidence: 99%
“…In addition, we assessed the potential of meningococcal PilQ to influence the integrity of the outer membrane, as viewed by its ability to allow passage of vancomycin. This new information is important for interpretation of 3D structural data, and further modelling of the PilQ complex (Collins et al, 2003(Collins et al, , 2004, as well as for studies of PilQ antigenicity and immunogenicity (Corbett et al, 1988;Hansen & Wilde, 1984). The findings may also be relevant for homologous secretins from the Gram-negative type II and III secretion systems.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis by single particle averaging methods suggested that the complex has C12 symmetry, and a three-dimensional reconstruction from a sample in negative stain at 25 Å resolution shows a bowl-like structure (11). To obtain more detailed structural information on the PilQ complex, we have applied cryo-negative staining in conjunction with single particle averaging methods to extend the resolution of the structure considerably to 12 Å.…”
mentioning
confidence: 99%